2004
DOI: 10.5558/tfc80573-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil disturbance and five-year tree growth in a montane alternative silvicultural systems (MASS) trial

Abstract: Ground-based forestry practices can negatively affect soil productivity by altering the physical, chemical, and biological properties of soil. The effect of soil disturbance on soil properties and tree growth was evaluated following single-pass hydraulic excavator and multiple-pass combined excavator and flexible track grapple skidder forwarding in four silvicultural systems treatments: Clearcut (CC), Green Tree Retention (GT), Patch Cut (PC), and Uniform Shelterwood (SW). The effectiveness of an excavator soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Any increases in seedling foliar N concentrations after clearcutting appear to last for up to four years after harvesting ( Fig. 8; Koppenaal and Hawkins 2000, Hawkins and Moran 2003, Maynard and Senyk 2004, which is fairly consistent with our results for N mineralization and availability in the soil. Changes in foliar N concentrations up to six years after harvesting suggest a possible response to a small assart effect that lasted from two to four years after harvesting.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Any increases in seedling foliar N concentrations after clearcutting appear to last for up to four years after harvesting ( Fig. 8; Koppenaal and Hawkins 2000, Hawkins and Moran 2003, Maynard and Senyk 2004, which is fairly consistent with our results for N mineralization and availability in the soil. Changes in foliar N concentrations up to six years after harvesting suggest a possible response to a small assart effect that lasted from two to four years after harvesting.…”
Section: Discussionsupporting
confidence: 81%
“…Foliar N concentrations at the time of planting were 2.15% and 1.99% for western hemlock and amabilis fir, respectively. Additional data for naturally-regenerated seedlings at two and five years (Koppenaal and Hawkins 2000;see Table 2 for statistical differences at two years) and planted seedlings at four years (Maynard and Senyk 2004;undisturbed microsites) are included as single points, represented by smaller symbols. Horizontal line at 1.15% indicates deficiency level for true fir (Powers 1983), and line at 1.45% indicates adequate level for western hemlock (Ballard and Carter 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greacen and Sands (1980) and Heilman (1981) reported that the elongation rate and penetration of primary roots are reduced when soil is compacted, inducing a lower uptake of nutrients and water (Kozlowski, 1999;Jordan et al, 2003). Compaction consequently leads to reduced tree growth (Gebauer and Martinková, 2005) and a higher tree seedling mortality (Brais, 2001;Stone and Kabzems, 2002;Maynard and Senyk, 2004). However, these effects are different depending on soil type, water regime and tree species (Jones, 1983;Gomez et al, 2002;Heninger et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…In the 1980s, total N concentration was determined by an automated semi-micro Kjeldhal method (McKeague 1978), whereas the 15-year resampling measurements were measured using a LECO N analyzer (LECO Corporation) (Maynard and Senyk 2004).…”
Section: Laboratory Analysismentioning
confidence: 99%